A Review of The Literature on Islamic Corporate Governance (ICG) In Waqf Entities - Arifin, Jaenal (ZISWAF, 2022)
Waqf is a social financial tool that is based on sharia and could help Indonesianefforts to fight poverty.Currently, however, the Waqf literacy index among Indonesians isnot particularlyhigh.The waqf topic has evolved in recent years in terms of research. Thisstudyaimstoanalyzeandevaluatepreviouslyconductedresearchbyidentifyingsimilarities between articles on the same topic. This study focuses on articles onhttps://www.connectedpapers.comthatcontainthekeywords"waqfinstitution"and"Islamic corporate governance (ICG)". According to the keywords, 19 articles werediscovered in total. This study's findings indicate that Islamic corporate governance (ICG)practice is a strategic issue in waqf institutions for enhancing public trust.